2022
DOI: 10.1200/jco.2022.40.4_suppl.436
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of durvalumab plus bevacizumab in unresectable hepatocellular carcinoma: Results from the phase 2 study 22 (NCT02519348).

Abstract: 436 Background: The phase 2 Study 22 trial (NCT02519348) investigated durvalumab (anti-programmed cell death ligand-1 [PD-L1] antibody) and tremelimumab (anti-cytotoxic T-lymphocyte associated antigen 4 antibody) as monotherapy, or durvalumab in combination with tremelimumab or bevacizumab (anti-vascular endothelial growth factor [VEGF] antibody), for the treatment of patients with unresectable hepatocellular carcinoma (uHCC). Results of Study 22 that evaluated durvalumab and tremelimumab as monotherapy or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A Phase 2 trial evaluated durvalumab and the anti-CTLA-4 monoclonal antibody tremelimumab or durvalumab in combination with tremelimumab or bevacizumab for the treatment of patients with unresectable HCC where the results indicated that combinatorial durvalumab and bevacizumab showed promising clinical safety and efficacy ( 126 ).…”
Section: Targeting Immune Checkpoints For the Treatment Of Hepatocell...mentioning
confidence: 99%
“…A Phase 2 trial evaluated durvalumab and the anti-CTLA-4 monoclonal antibody tremelimumab or durvalumab in combination with tremelimumab or bevacizumab for the treatment of patients with unresectable HCC where the results indicated that combinatorial durvalumab and bevacizumab showed promising clinical safety and efficacy ( 126 ).…”
Section: Targeting Immune Checkpoints For the Treatment Of Hepatocell...mentioning
confidence: 99%
“…Two studies focused on the efficacy and safety of nivolumab, and the remaining one focused on pembrolizumab. A total of seven studies used combination therapy of ICIs and angiogenesis inhibitory monoclonal antibodies (AI mAbs) as the treatment of intervention group [13,[35][36][37][38][39][40]. Three studies examined atezolizumab plus bevacizumab, followed by sintilimab plus IBI305 (n = 1), toripalimab plus bevacizumab (n = 1), ezabenlimab plus BI 836,880 (n = 1), and durvalumab plus bevacizumab (n = 1).…”
Section: Study Drugsmentioning
confidence: 99%